Production of biodiesel from crude palm oil by a sequential hydrolysis/esterification process using subcritical water - dos Santos, Letícia Karen [UNESP]; Hatanaka, Rafael Rodrigues [UNESP]; de Oliveira, José Eduardo [UNESP]; Flumignan, Danilo Luiz [UNESP] (Elsevier, 2019)
This paper investigates the biodiesel production by subcritical/chemical hydroesterification from crude palm oil. Hydroesterification is the innovation of biodiesel production in two-step: consists of hydrolysis of oil into free fatty acids (FFAs) in subcritical water and subsequent chemical esterification of FFAs into FAMEs (biodiesel). The purpose was to apply the experimental factorial design to evaluate the influence of reaction variables on the effectiveness of hydrolysis and determine the relationship of FFAs and FAMEs yields. Experiments were conducted in a batch reactor under various conditions and the optimal conditions (250 °C, 120 min, 100:1 water:oil molar ratio and 700 rpm) for hydrolysis was determined. The analyses indicated high FFAs yields (86 wt%). Esterification results revealed a conversion of the FFAs in 99.1 wt% of FAMEs in biodiesel production. This study shows that hydroesterification process produces biodiesel with excellent quality as well as traditional alkaline transesterification.
Keywords: Alkyl esters; Crude palm oil; Free fatty acids; Hydroesterification; Optimization; Response surface methodology